Pengaruh Strategi Pembelajaran Membaca dan Tingkat Skemata terhadap Pemahaman Bacaan Bahasa Arab - Hijriyah, Umi (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2015)
Abstract      The objective of this research is to find out the effects of the instructional strategies and the schemata level on the Arabic comprehension. The research was conducted at the Departement of Arabic Education, the State institute of Islamic Studies Raden Intan Lampung. The sample size was 35, which were selected at random. The results of the research showed that the DRTA strategy gave better result than SQ3R. The students with the high level of schemata taught with DRTA gave better result than the group with SQ3R. The group having low schemata level taught with DRTA provided lower result than the group with SQ3R. There was an interaction effect between the instructional strategy and the schemata level on the comprehensive skill of Arabic reading. Based on the finding it is concluded that the instructional strategy and the schemata level gave effects on the students’ reading comprehension. It is recommended the lecturers consider the schemata level with appropriate strategy.Keywords:Teaching Strategy of Reading, DRTA, SQ3R Schemata.